HEMODYNAMIC EFFECTS OF XENON ANESTHESIA IN CHILDREN - M. V. Bykov; V. G. Bagaev; V. G. Amcheslavskiy (Union of pediatricians of Russia, 2014)
The study was aimed at hemodynamic effects of xenon on operative interventions in children. Patients and methods: the study involved 30 5-17-year-old children - 10 (33.3%) girls and 20 (66.7%) boys with ASA score 1-3 admitted for surgical treatment. The children underwent endotracheal anesthesia with xenon-oxygen mixture (Xe:O2 = 60-65:30%) and fentanyl (2.5‑3.5  mcg/kg per hour) for the following operations: appendectomy - 10 (33.3%) patients, herniotomy - 8 (26.7%) patients, Ivanissevich procedure - 6 (20.0%) patients, plastic surgery of posttraumatic defects of skin and soft tissues - 4 (13.3%) patients, abdominal adhesiotomy - 2 (6.7%) patients. Central hemodynamics was studied echocardiographically (Philips HD 11, the Netherlands) using the Teichholz technique along the cephalocaudal axis (parasternal access). Results: the anesthesia was notable for hemodynamic stability during the operation: as a result, a statistically significant (p < 0.05) increase in systolic, diastolic and mean arterial pressure by 10, 18 and 17%, respectively, was observed. Conclusion: the analysis demonstrated that xenon anesthesia improves lusitropic myocardial function statistically significantly increasing cardiac output by 12% by way of increasing stroke volume by 30%.